My baby's father : unmarried parents and paternal responsibility - Waller, Maureen Rosamond, 1967- (Ithaca : Cornell University Press, 2002)
About one-third of births in the United States occur to unmarried parents. Evidence suggests that children who grow up in families headed by single parents have worse socioeconomic outcomes than those raised by married parents. "Fatherlessness" has become a byword in public debate and policymaking, yet fundamental questions about unmarried parents and their ideas of paternal responsibility remain unanswered. In My Baby's Father, Maureen R. Waller draws on interviews with unmarried parents whose children receive welfare to address several basic, vital questions: How do low-income mothers and fathers define the father's obligation to his children and explain irresponsible behavior among fathers? How do they negotiate private arrangements of paternal acknowledgment and support? And how do these informal practices interact with mandatory welfare and child-support regulations?The majority of research on low-income families focuses on single mothers. Waller's book also gives a voice to the fathers, historically either excluded from academic and policy discussions or simply characterized as "deadbeat dads" with no sense of paternal responsibility. By documenting the experiences of African-American and white parents simultaneously, Waller illustrates the extent to which beliefs and practices are likely to cut across racial lines. She also shifts the focus from teenagers to adults, who constitute the largest group of unmarried parents. My Baby's Father provides honest glimpses into the lives of unmarried parents. In addition, it offers specific recommendations for social policies that are both better suited to unmarried parents' socioeconomic situations and more responsive to the practices of responsible fatherhood in low-income families
Studying unmarried parents -- The separation of reproduction and marriage -- Models of fatherhood -- Interpreting paternal responsibility -- Departures from paternal responsibility -- Recognizing biological and social paternity -- Reconciling formal and informal systems of paternal support -- Conclusion : fatherhood, poverty, and public policy.
Includes bibliographical references (pages 185-195) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Unmarried fathers -- United States; Fatherhood; Pères célibataires -- États-Unis.; Paternité.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Fatherhood; Unmarried fathers; United States; Elterliche Sorge; Nichtehelicher Vater; Eheähnliche Gemeinschaft; USA; Ouders; Ongehuwden; Verantwoordelijkheid; Fatherhood; Electronic books